Why Do Cooperatives Emerge in a World Dominated by Corporations? The Diffusion of Cooperatives in the U.S. Bio-Ethanol Industry, 1978–2013 - Boone, Christophe; Özcan, Serden (Academy of Management Journal, 2014)
Given the strong economic disincentives that exist, why do cooperatives continue to emerge? And why is it that, in some communities, these cooperatives are collocated with their commercial counterparts, yet, in others, territorial partitioning occurs? In this paper, we develop a community ecology approach that integrates economic and sociological accounts of cooperatives, in an attempt to reconcile these contradictory observations. Using a detailed panel data set for the county-level founding process of cooperatives in the U.S. ethanol industry from 1978 to 2013, consistent with rational economic arguments, we find that the founding rate of cooperatives decreases in the presence of high, local, corporate ethanol production capacity. However, this negative competitive interdependence is attenuated in local communities where: (1) corporations represent a potential threat to the autonomy of local farmers, (2) there is a generally anti-corporate climate, and (3) there is a well-established organizational infrastructure supporting a cooperative ideology. Consistent with sociological theories that emphasize the mobilizing force of ideology, these local conditions spur and facilitate collective action among farmers to establish cooperatives in response to the local diffusion of corporations. We show further that the diffusion of plants owned by big business (oil and agribusiness) in communities characterized by a general anti-corporate climate especially promotes greater ideological contestation and the mobilization of resources to form cooperatives.